Global Linguistic Diversity for the Internet. - Anderson, Deborah (Communications of the ACM, 2005)
The article focuses on the use of the international character-encoding standard Unicode in computer software. The development and adoption of Unicode in computer software and fonts makes it possible to send and receive and read text electronically for hundreds of languages, all in their original scripts. The character-encoding standard underlying this multilingual capability is the Unicode Standard, which also has a parallel International Standard maintained by the International Organization for Standardization, called ISO/IEC 10646. Chinese, Greek, German, and Arabic can now be included in Web pages and email without the text getting garbled or marred with square boxes as placeholders. This multilingual capability frees users from ASCII's limited repertoire. Communicating with people in their own language and script also gives the world's diverse populations an electronic presence in the global information economy. Because Unicode is a single international standard, it marks a significant improvement over the earlier situation in computing where competing standards rendered the interchange of text often nearly impossible.